Feasibility study of a multimodal biometric authentication solution based on pointer dynamics and skin conductivity - Sá, Vítor J. (2013)
Due to the constant need to improve authentication systems, since they are constantly emerging new forms of intrusion, based on the current state of knowledge, we intend to study the acceptance of a recognition system based on the combination of two non-physical methods of biometric authentication: pointer dynamics and skin conductivity. With this combination, firstly, it is improved what each can offer individually and, secondly, the problem of replicability present in physical biometric is minimized. We conducted a survey with a representative sample of the Portuguese population, whose construction method and obtained results are presented in this article. We also present an introductory explanation of the involved technologies.